Effect of fluoride treatment on gene expression in tea plant (Camellia sinensis) - Qing-Sheng Li (Scientific Reports, 2017)
Abstract Tea plant is a typical fluorine (F) accumulator. F concentration in mature tea leaves is several hundred times higher than that in normal field crops. Long-term consumption of teas with high level F will increase the risks of dental and skeletal fluorosis. The mechanism of F accumulation in tea stands unclear. RNA-Seq and digital gene expression (DGE) techniques were used to investigate the effect of F on the differential expressions of transcriptome in tea plant. The results showed that F content in mature tea leaves was increased with increase in F concentration of cultural solution and duration of F treatment time. Based on comparison with data of GO, COG, KEGG and Nr databases, 144 differentially expressed unigenes with definite annotation were identified. Real-time reverse transcription PCR (qRT-PCR) was used to validate the effect of F on expression of 5 unigenes screened from the 144 unigenes. F treatment induced the expression of defense genes such as receptor-like kinases (RLKs) and U-box domain-containing protein. Based on the present study, F uptake is considered to be related to calcium-transporting ATPase, especially autoinhibited Ca2+ ATPase (ACAs) which was activated by the RLKs and worked as a carrier in uptake of F by tea plant.